Analisis Ketidakstabilan Tegangan dan Frekuensi Pada Pembangkit Listrik Tenaga Mikrohidro Soko Kembang - Nurul Dyah Pratiwi; Isdiyato Isdiyato (Sekolah Tinggi Teknik PLN, 2019)
Microhydro power plant (MPP) is a small-scale power plant that uses water energy. The process of energy change occurs in a device called a synchronous generator. when the synchronous generator is given an arbitrary load, then the voltage will change. These results cause voltage and frequency instability. This research was conducted to analyze the voltage and frequency instability in MPP. The research method used in this research is descriptive quantitative approach in the village of Soko Kembang, Petungkriyono District, Pekalongan Regency, Central Java. This study provides an overview and explanation of the problems regarding the voltage and frequency instability of Micro Hydro Power Plants. The results of this study are the highest and lowest voltage / frequency instability values, namely 235 volts / 51 Hz and 160 volts / 44 Hz, due to the influence of changes in load current, which can affect the rotational speed of the generator changes, resulting in unstable voltage and frequency generated by the generator, the rotational speed of the generator changes, resulting in unstable voltage and frequency generated by the generator. The solution is add water power to rotate the shaft of the turbine and generator to be tighter, so that it can reduce the value of the decrease in electric power by losses to the turbine and generator. Large electric power can increase voltage and frequency without having to adjust the load, and the need for improvement of the ELC system in order to get a more effective value of voltage and frequency stability.